A New Class of Amide Ligands Enable Cu‐Catalyzed Coupling of Sodium Methanesulfinate with (Hetero)aryl Chlorides. Issue 11 (23rd October 2017) - Ma, Dawei; Niu, Songtao; Zhao, Jinlong; Jiang, Xi; Jiang, Yongwen; Zhang, Xiaojing; Sun, Tiemin
Abstract : ((2 S, 4 R )‐4‐Hydroxy‐ N ‐(2‐methylnaphthalen‐1‐yl)pyrrolidine‐2‐carboxamide (HMNPC), an amide derived from 4‐hydroxy‐ L ‐proline and 2‐methyl naphthalen‐1‐amine, is a powerful ligand for Cu‐catalyzed coupling of (hetero)aryl halides with sulfinic acid salts, allowing for first time the metal‐catalyzed coupling of (hetero)aryl chlorides and NaSO2 Me. A considerable number of (hetero)aryl chlorides worked well, providing the pharmaceutically important (hetero)aryl methylsulfones in good to excellent yields. Abstract :